Evaluación de un prospecto exploratorio en el bloque puntero en la cuenca de los llanos orientales con base en lineamiento Project Management Institute (2017)
In the present work a description of the different methodologies for the direction of projects that are currently used is made, such as the logical framework approach, the standards of the international association for project management (IPMA) and those established by its chapter. in the United Kingdom, the partnership for project management (APM), analysis and evaluation services by the IPA company and finally the standard established by the project management institute (PMI) is described. Then, relevant definitions of project management are stated. Due to the high degree of uncertainty in project execution in the oil industry, many companies around the world have embraced the use of different project management methodologies, including organizations that operate in Colombia. Each of these built its own model based on existing methodologies, for example ECOPETROL structured its model based on certain PMI guidelines.